The Potential of Geoparks for Sustainability Learning Resources in Elementary Schools: A Review - Styo Mahendra Wasita Aji; Herti Prastitasari; Miftha Huljannah; Nurul Julaifah (Universitas Negeri Malang, 2026)
Abstract: The environment can be a source of learning that is relevant to elementary school students according to their developmental stages. The purpose of this study is to describe the role of geoparks for education so far, to describe geopark opportunities as a learning resource in elementary schools, and to describe the challenges of geoparks as a learning resource in elementary schools. The research is based on a systematic method of literature review that refers to the PRISMA flow. Systematic literature review consists of identification, screening, and included steps. The reviewed articles went through the screening and study of the PRISMA pipeline with the Scopus database between 2020 until 2025. The results of the study show that there is a role that has been carried out by geoparks as a place that contains knowledge and values about sustainability, the potential of geoparks as a sustainability-based learning resource, and challenges as a learning resource in elementary schools with sustainability values that require regulatory certainty as a form of community involvement in preserving geoheritage heritage. The next recommendation is the potential for the development of teaching materials or a geopark-based learning model that can be carried out. Abstrak: Lingkungan dapat menjadi sumber pembelajaran yang relevan bagi siswa sekolah dasar sesuai dengan tahap perkembangannya. Tujuan penelitian ini adalah untuk menggambarkan peran geopark dalam pendidikan hingga saat ini, mengidentifikasi potensi geopark sebagai sumber daya pembelajaran di sekolah dasar, serta mengidentifikasi tantangan geopark sebagai sumber daya pembelajaran di sekolah dasar. Penelitian ini didasarkan pada metode tinjauan pustaka sistematis yang mengacu pada alur PRISMA. Tinjauan pustaka sistematis terdiri dari tahap identifikasi, penyaringan, dan inklusi. Artikel-artikel yang ditinjau telah melalui proses penyaringan dan analisis menggunakan alur kerja PRISMA dengan basis data Scopus dari tahun 2020 hingga 2025. Hasil penelitian menunjukkan bahwa geopark memiliki peran sebagai tempat yang menyimpan pengetahuan dan nilai-nilai tentang keberlanjutan, potensi geopark sebagai sumber belajar berbasis keberlanjutan, serta tantangan dalam penggunaannya sebagai sumber belajar di sekolah dasar yang mengedepankan nilai-nilai keberlanjutan; hal ini memerlukan kepastian regulasi sebagai bentuk keterlibatan masyarakat dalam melestarikan warisan geologi. Rekomendasi selanjutnya adalah potensi pengembangan bahan ajar atau model pembelajaran berbasis geopark yang dapat diimplementasikan.